Myrmecofauna (Hymenoptera: Formicidae) of the Isabel Island Nacional Park, Sea of Cortés, Mexico - CUPUL-MAGAÑA, FABIO GERMÁN; REYES-JUÁREZ, ABRAHAM (Revista Colombiana de Entomología, 2005)
During 2004 the presence of 12 species of ants in the Isabel Island National Park, Sea of Cortés, Mexico, was reported systematically. A theoretical linear model was applied to estimate the number of species of ants that the island can support based on its area. The model calculated a value of 12.50 species for an area of 1.94 km2. The agreement between this theoretical value, the total species recorded, and the asymptotic tendency of the species-accumulation curve, allowed us to suggest that the listed diversity of ants is close to the maximum that can be observed. Nevertheless, it is also discussed how sampling, plant diversity or the presence of marine birds, can affect positively or negatively the diversity of ants.